Atlas revolution in the brazilian economy - Laisla Cardoso dos Santos, Lorraine; Miranda de Souza, Camilla (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2024)
This article aims to study the effects that state intervention has on economic growth and how this parallels the Brazilian society depicted in the book "Atlas Shrugged" by Ayn Rand. It demonstrates how intervention generates bureaucracy, leading significant entrepAbstract: This article aims to study the effects that state intervention has on economic growth and how this parallels the Brazilian society depicted in the book "Atlas Shrugged" by Ayn Rand. It demonstrates how intervention generates bureaucracy, leading significant entrepreneurs to distrust the national economic market, resulting in an intellectual exodus due to the state’s interference in matters outside its purview. To underscore the importance of the free market, the article proposes an analysis of antitrust legislation and aspects of labor laws, revealing how such interference violates principles such as free enterprise and free competition. Additionally, this work is the culmination of research and studies conducted over the past five years, which have been updated and compiled to broaden the discourse on Rand’s philosophical contributions and analyze their implications in the Brazilian economic landscape. Finally, it examines how such intervention can detrimentally impact the country’s economic growth, precipitating an economic and social crisis that transforms Brazilian society into the chaos described by Ayn Rand refers to distrust of the national economic market, resulting in an intellectual exodus due to the state’s interference in matters outside its purview. To underscore the importance of the free market, the article proposes an analysis of antitrust legislation and aspects of labor laws, revealing how such interference violates principles such as free enterprise and free competition. Additionally, this work is the culmination of research and studies conducted over the past five years, which have been updated and compiled to broaden the discourse on Rand’s philosophical contributions and analyze their implications in the Brazilian economic landscape. Finally, it examines how such intervention can detrimentally impact the country’s economic growth, precipitating an economic and social crisis that transforms Brazilian society into the chaos described by Ayn Rand.